The REFORM study protocol: a cohort randomised controlled trial of a multifaceted podiatry intervention for the prevention of falls in older people. Issue 12 (17th December 2014) - Cockayne, Sarah; Adamson, Joy; Corbacho Martin, Belen; Fairhurst, Caroline; Hewitt, Catherine; Hicks, Kate; Hull, Robin; Keenan, Anne Maree; Lamb, Sarah E; Loughrey, Lorraine; McIntosh, Caroline; Menz, Hylton B; et al.
Abstract : Introduction: Falls and fall-related injuries are a serious cause of morbidity and cost to society. Foot problems and inappropriate footwear may increase the risk of falls; therefore podiatric interventions may play a role in reducing falls. Two Cochrane systematic reviews identified only one study of a podiatry intervention aimed to reduce falls, which was undertaken in Australia. The REFORM trial aims to evaluate the clinical and cost-effectiveness of a multifaceted podiatry intervention in reducing falls in people aged 65 years and over in a UK and Irish setting. Methods and analysis: This multicentre, cohort randomised controlled trial will recruit 2600 participants from routine podiatry clinics in the UK and Ireland to the REFORM cohort. In order to detect a 10% point reduction in falls from 50% to 40%, with 80% power 890 participants will be randomised to receive routine podiatry care and a falls prevention leaflet or routine podiatry care, a falls prevention leaflet and a multifaceted podiatry intervention. The primary outcome is rate of falls (falls/person/time) over 12 months assessed by patient self-report falls diary. Secondary self-report outcome measures include: the proportion of single and multiple fallers and time to first fall over a 12-month period; Short Falls Efficacy Scale—International; fear of falling in the past 4 weeks; Frenchay Activities Index; fracture rate; Geriatric Depression Scale; EuroQoL-five dimensional scale 3-L; health service utilisation at 6 and 12 months. A qualitative study will examine the acceptability of the package of care to participants and podiatrists. Ethics and dissemination: The trial has received a favourable opinion from the East of England—Cambridge East Research Ethics Committee and Galway Research Ethics Committee. The trial results will be published in peer-reviewed journals and at conference presentations. Trial registration number: Current Controlled Trials ISRCTN68240461assigned 01/07/2011.